Описание личинки хрущевика Tanyprocius Araxis (Coleoptera, Scarabaeidae) - Калашян, М.Ю.; Мкртчян, Л.П. (Вестник зоологии, 1993)
Description is based upon 7 larva specimens from Gorovan Sands near Vedi, Armenia.